Thermally exfoliated graphene oxide doped microporous bio-nanocomposite hydrogel: A promising substrate for biomedical application - Rani S.; Bandyopadhyay-Ghosh S.; Ghosh S.B.; Singh P.; Dubey A.K.; Liu G. (My University, 2025)
Hydrogels have demonstrated significant promise as flexible/wearable sensors for the diagnosis, monitoring, and delivery of personalized medicine for health issues and deficiencies. To this end, a novel approach was employed towards the development of a hybrid hydrogel nanocomposite-based biosensing substrate. The hierarchical hydrogel matrix derived by using polyaniline (PANI)/polyvinyl-alcohol (PVA) biopolymer-matrix, was reinforced with in-house synthesized thermally exfoliated graphene-oxide (TEGO). Fourier transform infrared spectroscopy (FT-IR) confirmed the interfacial-interactions between hydroxyl groups and functional groups of TEGO, a conducive property for immobilization and catalytic activities. X-ray photoelectron spectroscopy (XPS) investigation of the developed nanocomposite hydrogel demonstrated that the addition of nanofiller facilitated the ordered structure of nanocomposite hydrogel. Further, field emission scanning electron microscopy (FE-SEM) investigations revealed interconnected porous microstructure of the nanocomposites, assisted by nucleating effect of TEGO, a supporting micro-environment for the transportation of biomolecules. Impedance analysis and hall effect studies showed that the nanocomposite hydrogel substrate was highly conductive. In vitro cytocompatibility results demonstrated excellent biocompatibility of the bio-nanocomposite hydrogels. Cyclic-voltammetry analysis indicated a reduction in current on the surface due to long-range shattered conjugated network of TEGO and PANI in presence of functional groups. Overall, this study indicates that developed bio-nanocomposite hydrogel substrates are promising candidates for biomedical applications. © The Author(s) 2024.